How to Harvest Deep Inferior Epigastric Perforator Free Flap - Mohamad Rachadian Ramadan; Khanza Isdiharana Keusuma; Gary Ali; Anisa Ayu Maharani; Ayu Putri Balqis Sarena (Jurnal Plastik Rekonstruksi, 2025)
Summary : The Deep Inferior Epigastric Perforator (DIEP) free flap is a microsurgical breast reconstruction technique that uses skin and subcutaneous fat from the lower abdomen while preserving the rectus abdominis muscle. This approach provides a natural breast mound with minimal donor-site morbidity compared to TRAM flaps, reducing risks of muscle weakness and abdominal wall hernia. Advantages include improved postoperative recovery, better abdominal contour, and long-lasting aesthetic results, as the reconstructed breast maintains its volume over time. However, it is technically demanding, requires longer operative time, and carries risks of flap loss or vascular complications if microsurgery fails. The procedure involves dissecting perforator vessels from the deep inferior epigastric system, transferring the tissue to the chest, and connecting vessels under a microscope. Expected outcomes include a soft, natural breast shape with improved patient satisfaction, though surgical expertise and careful patient selection are essential to minimize complications and ensure optimal results.